Adult Neural Stem Cells Bridge their Niche - Fuentealba, Luis C. (2012)
Major developments in the neural stem cell (NSC) field in recent years provide new insights into the nature of the NSC niche. In this perspective, we integrate recent anatomical data on the organization of the two main neurogenic niches in the adult brain, the ventricular-subventricular zone (V-SVZ) and the subgranular zone (SGZ), with signaling pathways that control the behavior of NSCs. NSCs in the adult brain stretch into physiologically distinct compartments of their niche. We propose how adult NSCs’ unique morphology may allow these cells to integrate multiple signaling pathways arising from unique locations of their niche.